Answer:
Explanation:
4x – 9y = 7
–2x + 3y = 4 (2)
You want to eliminate the x-terms when adding to the first equation, so you have to multiple both sides of the equation (2) by 2 like:
4x – 9y = 7
–4x + 6y = 8
-----------------------------(add)
0 - 3y = 15
or y = -5, and x = - 19/2
But if you want to eliminate the y-terms when adding to the first equation, so you have to multiple both sides of the equation (2) by 3, like
4x – 9y = 7
-6x + 9y = 12
-----------------(add)
-2x + 0 = 19
or x = - 19/2 and y = - 5